PENGARUH TINGKAT TUMBUHNYA EKONOMI DAN UPAH MINIMAL PADA PENGANGGURAN DI KABUPATEN BULUNGAN - fauziah, suud ema (2020)
The most influential indicator of success in the economic growth cycle is the most important natural resources available, followed by adequate human resources to the most important factor in economic growth. The concept of economic growth is not based on the number of human resources, and is not measured by quality alone but minimizes the emphasis on the efficiency of the quality of human resources. The lower the quality of human resources (HR) so that it affects the low productivity and the role of human resources who perform work activities as workers who carry out the process or who do the production. In this study, the expected goal is to determine the distribution, classification, and influence of economic growth, minimum wage, of the level of unemployment in Bulungan District 2002-2014. This research uses Multiple linear Regression (Multiple Regression) research methods. Data analysis by the formulation of the problem, and the purpose of the study is using objectives is to use the model of the Double Regression Equation and t-test. The results classification shows that in the hypothesis test it is known that economic growth and minimum wages have the same effect on unemployment in Bulungan District. The relationship is characterized by a positive number shown by the minimum wage, if the minimum wage, which, if the minimum wage rises, unemployment increases.